On sums of odd and even terms of the K-Fibonacci numbers - Panwar, Yashwant; Rathore, Gajendra P.; Chawla, Richa (Global Journal of Mathematical Analysis, 2014)
In this paper, we define some properties of sums of k-Fibonacci numbers. Also we present the sum of consecutive members of k-Fibonacci numbers and the same thing for even and for odd k-Fibonacci numbers. Mainly, Binet’s formula will be used to establish properties of k-Fibonacci numbers. Keywords: K-Fibonacci Numbers, K-Lucas Numbers, Binet’s Formula.